The Impact of Human Resource Competency and Transformational Leadership on Employee Performance with Motivation as a Mediating Variable - Wijayanti, Anies; Witjaksono, Andre Dwijanto; Kistyanto, Anang (Universitas Pendidikan Indonesia, 2024)
Transformational Leadership at DLH has been applied but there is still no evidence that the application of transformational leadership at DLH Kota Surabaya can improve overall employee performance. This research aims to analyze the influence of competence and transformational leadership on employee performance through the role of motivation as an intervening variable using the SEM-PLS method on a sample of DLH Surabaya City employees. SEM-PLS is used because of its ability to obtain relationship results between variables. The results show good validity and reliability of the instrument. Motivation variables explain 47.6% of employee performance, while competence and transformational leadership explain 52% of motivation. In a case study at DLH Kota Surabaya, it was found that competence had a positive and significant effect on employee performance and motivation. Transformational leadership has a positive and significant effect on motivation but not employee performance. Motivation does not have a significant effect on employee performance and is not effective as a mediating variable between competence and performance, as well as transformational leadership and performance. Factors such as rigid bureaucratic structures and lack of effective training contributed to these findings. These findings are important for policy makers to develop more effective HR management and leadership strategies.